2017
DOI: 10.1007/s12011-017-1206-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arsenic Trioxide on INF-gamma Gene Expression in MRL/lpr Mice and Human Lupus

Abstract: Arsenic trioxide (As2O3; ATO), a traditional Chinese medicine, is used to treat patients with acute promye-locytic leukemia, while its application for treatment of systemic lupus erythematosus (SLE) is still under evaluation. The high expression of INF-gamma (INF-γ) is a primary pathogenic factor in SLE. It is found that ATO can reduce INF-γ expression levels in lupus-prone mice, whereas it is not clear whether ATO has the same effect on SLE patients. Therefore, this study was to investigate the underlying mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
5
6
0
Order By: Relevance
“…Our data demonstrated that treatment with ATO decreased the mRNA levels of inflammatory cytokines in the spinal cord and reduced the concentration of IFN-γ in the serum of EAE mice. Consistent with our findings, studies have reported that ATO reduced inflammation in splenocytes of MRL/lpr mice and human lupus peripheral blood mononuclear cells by reducing the expression levels of INF-γ [34]. Collectively, the therapeutic effects of ATO in our study may be partially due to the lower expression levels of proinflammatory cytokines, such as IL-2, IFN-γ, IL-1β, IL-6, and TNF-α.…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrated that treatment with ATO decreased the mRNA levels of inflammatory cytokines in the spinal cord and reduced the concentration of IFN-γ in the serum of EAE mice. Consistent with our findings, studies have reported that ATO reduced inflammation in splenocytes of MRL/lpr mice and human lupus peripheral blood mononuclear cells by reducing the expression levels of INF-γ [34]. Collectively, the therapeutic effects of ATO in our study may be partially due to the lower expression levels of proinflammatory cytokines, such as IL-2, IFN-γ, IL-1β, IL-6, and TNF-α.…”
Section: Discussionsupporting
confidence: 92%
“…Women may convert As to particularly immunosuppressive metabolites, and long-term exposure of men to As during aging may suppress these autoantibodies. These findings are consistent with the association between urinary As and decreased protective antibody response to mumps vaccine [25] and to challenge with purified protein derivative in BCG-vaccinated Bangledesh children [18], and that sex-specific differences may complicate this effect [26], In direct tests arsenic trioxide inhibited interferon-γ synthesis in vitro by lymphocytes from patients with SLE [27] and prolonged survival and decreased anti-nDNA production in lupus-prone mice [28], possibly by inhibiting inflammasome activation [29].…”
Section: Discussionsupporting
confidence: 82%
“…Our data demonstrated that treatment with ATO decreased the mRNA level of inflammatory cytokines in the spinal cord and reduced the concentration of IFN-γ in the serum of EAE mice. Consistent with our findings, studies have reported that ATO reduced inflammation in splenocytes of MRL/lpr mice and human lupus peripheral blood mononuclear cells by reducing the expression level of the INF-γ [33]. Collectively, the therapeutic effects of ATO in our study may be partially due to lower expression of proinflammatory cytokines, such as IL-2, IFN-γ, IL-1β, IL-6, and TNF-α.…”
Section: Discussionsupporting
confidence: 92%